A comprehensive study of calcific aortic stenosis: from rabbit to human samples - Laura Mourino-Alvarez; Montserrat Baldan-Martin; Tamara Sastre-Oliva; Marta Martin-Lorenzo; Aroa Sanz Maroto; Nerea Corbacho-Alonso; Raul Rincon; Tatiana Martin-Rojas; Luis Fernando Lopez-Almodovar; Gloria Alvarez-Llamas; Fernando Vivanco; Luis Rodriguez Padial; et al. (The Company of Biologists, 2018)
The global incidence of calcific aortic stenosis (CAS) is increasing owing, in part, to a growing elderly population. The condition poses a great challenge to public health, because of the multiple comorbidities of these older patients. Using a rabbit model of CAS, we sought to characterize protein alterations associated with calcified valve tissue that can be ultimately measured in plasma as non-invasive biomarkers of CAS. Aortic valves from healthy and mild stenotic rabbits were analyzed by two-dimensional difference gel electrophoresis, and selected reaction monitoring was used to directly measure the differentially expressed proteins in plasma from the same rabbits to corroborate their potential as diagnostic indicators. Similar analyses were performed in plasma from human subjects, to examine the suitability of these diagnostic indicators for transfer to the clinical setting. Eight proteins were found to be differentially expressed in CAS tissue, but only three were also altered in plasma samples from rabbits and humans: transitional endoplasmic reticulum ATPase, tropomyosin α-1 chain and L-lactate dehydrogenase B chain. Results of receiver operating characteristic curves showed the discriminative power of the scores, which increased when the three proteins were analyzed as a panel. Our study shows that a molecular panel comprising three proteins related to osteoblastic differentiation could have utility as a serum CAS indicator and/or therapeutic target.